Actions to be taken in Mexico towards education 4.0 and society 5.0 - Jesus Alvarez-Cedillo; Mario Aguilar-Fernandez; Raul Jr. Sandoval-Gomez; Teodoro Alvarez-Sanchez (Institute of Advanced Engineering and Science, 2019)
Education in Mexico has not evolved in the way it is taught and evaluated. In the historical moment that postmodernism enters, it has not been possible to adapt to Information and Communication Technologies(ICT), or rapid technological innovation, or changes and trends in the industry, to the sharing economy or the rise of distance races. In its analysis, an essential deficiency is detected in the current education models, and it is detected that educational freedom is nil or scarce, which has led to poor student performance, high youth unemployment, which cause severe social problems and the economy of the economy. The current government is working closely with the private sector to connect education and promote employment. It is necessary to grant public schools more autonomy, freedom and responsibility. This paper explains how to act so that Mexico can adapt education 4.0 with solid steps to reach society 5.0.